“Análisis de las secuencias codificantes de los genes relacionados con la respuesta inmunitaria a los parásitos trematodos” - Ruiz Mera, María Belén (2021)
The present research project was developed based on a documentary methodology, where the coding sequences of the genes related to the immune response of the Trematode parasites for different species of animals were analyzed. A database was prepared, which is made up of: gene, animal species, location of the gene or chromosome (description, location, and area), exon related to immunity, intron related to immunity, protein sequence, immunity with which is related, pathology with which it was evidenced and referenced. The genes investigated were those that are directly related to immunity against trematode parasites in different species of animals, these genes are IFN-γ (bovine, ovine, porcine, equine, feline, lagomorphic, and South American camelid), IL 4 (ovine, equines, canines, and birds), IL-10 (birds), IL-13 (Birds) and TCD4 (Birds). The information collected in this research was obtained through the National Center for Biotechnology Information (NCBI), where specific information could be found on the genes related to immunity against fluke parasites of the different animal species covered in this research project. 26 genes were investigated (several genes in different species) of which 54% (14 genes) information was found and of these, it was identified that 77% (10 genes) of the localizations related to immunity are found in the exons and the remaining 33% (3 genes) are found in introns.